2009
DOI: 10.1152/ajpcell.00452.2008
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in Ca2+ homeostasis and contractility in gallbladder smooth muscle

Abstract: Relatively little is known about the contribution of Ca(2+)-dependent and -independent mechanisms in the contractility of neonatal gastrointestinal smooth muscle. We therefore studied Ca(2+) homeostasis and Ca(2+) sensitization mechanisms in 10-day-old and adult guinea pig gallbladder smooth muscle to elucidate developmental changes in these processes. Gallbladder contractility was evaluated by isometrical tension recordings from strips, intracellular Ca(2+) concentration was estimated by epifluorescence micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Here, we show that aging displays opposite effects since it leads to an impairment of calcium sensitization pathways that is translated into hypocontractility of the gallbladder. These findings, together with results obtained in gallbladders from newborn guinea pigs (Camello-Almaraz et al 2009), draw the whole picture about the state of calcium sensitization along life. In guinea pig gallbladder, calcium sensitization pathway increases from birth to adult ages (CamelloAlmaraz et al 2009) and after that it suffers a decline.…”
Section: Discussionsupporting
confidence: 61%
“…Here, we show that aging displays opposite effects since it leads to an impairment of calcium sensitization pathways that is translated into hypocontractility of the gallbladder. These findings, together with results obtained in gallbladders from newborn guinea pigs (Camello-Almaraz et al 2009), draw the whole picture about the state of calcium sensitization along life. In guinea pig gallbladder, calcium sensitization pathway increases from birth to adult ages (CamelloAlmaraz et al 2009) and after that it suffers a decline.…”
Section: Discussionsupporting
confidence: 61%
“…Consistent with previous studies with different neonatal SMs (8,9,11,12,14,31), we found that actin and myosin expression and specific active peak force elicited by KCl and carbachol at optimal length were lower compared with the adult. Specific force takes into account that the mechanical output depends on multiple factors, some of which are difficult to assess.…”
Section: Excitation Contraction Coupling In Relation To Contractile Psupporting
confidence: 92%
“…Although several studies addressed different aspects of the fetal and postnatal maturation of innervation, electrical activity, and global contractile activity of the GIT (5-7), only few studies addressed in some depth the properties of the downstream effector, the SM. Investigations from avian (8) and mammalian stomach (9)(10)(11), and guinea pig gallbladder (12) as well as from non-GIT organs like urinary bladder (13,14), revealed major differences between neonatal and adult tissues as regards electro-and pharmacomechanical coupling (14,15), protein composition, and functional properties of the contractile apparatus (14)(15)(16)(17). Interestingly, despite the widespread use of transgenic mouse models to investigate the contribution of individual proteins to the regulation of contraction (18)(19)(20), we are not aware of a systematic evaluation of biomechanics of the neonatal ileum coincident with its tissue architecture and protein composition of the contractile machinery.…”
mentioning
confidence: 99%
“…Maturational differences in the calcium sensitization and desensitization pathways, as well as calcium handling, have been reported for other smooth muscle tissues, e.g., gallbladder (24). It has also been reported that ovine fetal cerebral arteries exhibit greater calcium sensitivity and http://physiolgenomics.physiology.org/ desensitization than do the mature arteries (89,148,186), though the mechanism has yet to be identified.…”
Section: Blood Vessel Developmentmentioning
confidence: 94%